Joining NATO is Declared a Strategic Aim of Ukraine - Liudmyla Chekalenko; Mariya Vasylyeva (Vasyl Stefanyk Precarpathian National University, 2017)
The authors present their vision of the international and Ukraine's national security in the 21st century context, analyze new challenges and security threats searching for the reason of collapse of the modern security system. All the research conclusions are based on the national security situation in nowadays Ukraine.